ОҚЫЎШЫЛАРДА ТАРИЙХЫЙ БИЛИМЛЕРДИ ҚӘЛИПЛЕСТИРИЎДЕ ИННОВАЦИЯЛЫҚ ТЕХНОЛОГИЯЛАРДЫҢ ОРНЫ (VI класс мысалында) - Ганиев, Т.С. (FAN va JAMIYAT, 2019)
The article deals with the advantages of pedagogical technologies and using interactive methods at the lessons in History.